The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/nu12102926
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Rice-Centered Diet on the Quality of Sleep in Association with Reduced Oxidative Stress: A Randomized, Open, Parallel-Group Clinical Trial

Abstract: Previously, we found that a Japanese diet was associated with psychological status, and a combination of rice and miso was related to mental and physical health. We hypothesized that the intake of a rice-based diet affected mental and physical health and aimed to investigate the consequences of a dietary intervention with rice. We conducted a randomized, open-label, parallel-group clinical trial that included 60 participants, who were randomly assigned to receive either rice-based meals or meals with other cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…In South Korea and Japan, rice is deeply associated with cultural identity, memories of family, and the community [ 23 ]. Healthy homemade meals are mostly perceived to be rice-based meals, which tend to be more balanced, higher in nutrients, and lower in calories than Western foods; several studies have been published on the association of rice-centered Japanese diet with the quality of life, sleep, impulsivity, depressive symptoms, and biochemical changes [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Korea and Japan, rice is deeply associated with cultural identity, memories of family, and the community [ 23 ]. Healthy homemade meals are mostly perceived to be rice-based meals, which tend to be more balanced, higher in nutrients, and lower in calories than Western foods; several studies have been published on the association of rice-centered Japanese diet with the quality of life, sleep, impulsivity, depressive symptoms, and biochemical changes [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…24, IMB Corp), incorporating a range of statistical tests, such as 2-tailed t tests, chi-square tests, and repeated-measures ANOVA. Repeated-measures ANOVA was specifically used to compare 2 groups of repeated observations captured at baseline, after 1 week of gameplay, and after 3 weeks of gameplay in the IIG and at the corresponding time points in the WLG.…”
mentioning
confidence: 99%
“…[6][7][8][9] Two large studies concluded a positive impact of fruits and vegetables on sleep quality among older adults 10 and university students. 11 Smaller studies found positive associations between sleep quality and other types of food such as milk, 8,12 cherries 8,9 and rice 13 in older adults. Other studies reported a positive impact of nutrients like protein 14,15 or even dietary patterns such as the Mediterranean diet 16,17 in middle aged and older participants.…”
Section: Introductionmentioning
confidence: 99%